2014
DOI: 10.4049/jimmunol.1302389
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Are the Crucial Antitumor Mediators When STAT3-Mediated Immunosuppression Is Blocked in Hepatocellular Carcinoma

Abstract: STAT3 is highly activated in a wide variety of cancers and functions to promote tumor survival. We previously reported that blocking STAT3 activation inhibited human hepatocellular carcinoma (HCC) growth in vitro, but whether this treatment also triggered antitumor immune responses in vivo remained unknown. In this study, we found that blocking the STAT3 pathway in HCC cells dramatically inhibited murine HCC growth in vivo and prolonged survival of tumor-bearing mice. Importantly, the presence of STAT3-blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 34 publications
2
61
0
Order By: Relevance
“…10). Inhibition of STAT3 activity has been shown to sensitize HCC cells to NK cell-mediated cytotoxicity (45). Interestingly, our data show that STAT3 activity is reduced in the CCL2 nab treated mice tumors (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…10). Inhibition of STAT3 activity has been shown to sensitize HCC cells to NK cell-mediated cytotoxicity (45). Interestingly, our data show that STAT3 activity is reduced in the CCL2 nab treated mice tumors (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of immune cells with distinct functional properties in different tumour areas suggests that tumours can actively generate diverse immune contexts to foster disease progression. Interestingly, several pro‐oncogenic molecules, such as STAT3, JNK, and β‐catenin, are also active regulators of immune cells . Conversely, several immune modulators, including B7‐H1, are also highly expressed by tumour cells .…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of immune cells with distinct functional properties in different tumour areas suggests that tumours can actively generate diverse immune contexts to foster disease progression. Interestingly, several pro-oncogenic molecules, such as STAT3, JNK, and β-catenin, are also active regulators of immune cells [14][15][16][17][18][19][20][21]. Conversely, several immune modulators, including B7-H1, are also highly expressed by tumour 320 L Zhao et al As a high-affinity receptor for hepatocyte growth factor (HGF) [26], c-Met is widely expressed by a variety of human solid tumours and plays a critical role in regulating the growth and epithelial-mesenchymal transition (EMT) of tumour cells [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of STAT3‐blocked HCC cells, NKG2D ligands were upregulated, transforming growth factor‐β (TGF‐β) and interleukin (IL)‐10 expression was reduced, and type I IFN was induced, thus facilitating NK cell activation. These findings indicated that blocking STAT3 in HCC cells could initiate innate immunity in vivo . In a panel of HCC cell lines, human allogeneic suicide gene‐modified killer cells showed an IL‐2‐dependent, and non‐MHC class I‐restricted cytotoxicity in vitro and in vivo , mainly mediated by NK and NK‐like T cells …”
Section: Immunotherapeutic Strategiesmentioning
confidence: 92%